Corporate Social Responsibility PT. Semen Tonasa dalam Penanganan Fakir Miskin di Wilayah Pesisir Desa Bulu Cindea Kabupaten Pangkep Sulawesi Selatan - Rachmat Parawangsa; Indra Lestari (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2021)
This study discusses the implementation of empowerment of poor women’s business groups thought PT Semen Tonasa’s Corporate Social Responsibility (CSR) in the coastal area of Bulu Cindea Village, Pangkep Regency. The research was conducted with the aim of describing and improving information broadly and in dept( qualtitative descriptive) on the Onasa Mandiri Program in the form of training and procurement of womend’s business groips. The research results provide a specific detailed description including; poverty condition, realization of the CSR fund budget, The TOnasa Mandiri Program, Impelmentation of community empowerment programs, as wel as obstacles to community empowerment